BATASAN GURU DALAM PEMBERIAN SANKSI DAN KESEIMBANGAN DENGAN PENDIDIKAN KARAKTER SISWA TINGKAT SEKOLAH DASAR - Hajar Nurul Izzati; Zahara Edlin Putri; Yospi Merlin; Beby Oktavia; M. Jaya Adi Putra; Mutia Yulita Sari (CV. ADIBA ASIHA AMIRA, 2024)
The application of limits in giving sanctions, balanced with character education, aims to create fair and educational discipline without harming students' emotional development. These limits help teachers maintain a balance between enforcing rules and fostering positive character traits, such as responsibility, discipline, and empathy. Thus, sanctions are given as a means of learning, not merely as punishment. The aim of this research is to examine how teachers understand the limits of giving sanctions and the importance of comparing sanctions with character education for students. This research uses qualitative methods, collecting data through direct face-to-face interviews. This article presents a discussion regarding the limitations in providing sanctions and character education for students. The results of this research show that providing appropriate sanctions, balanced with character education, has a positive impact on changes in elementary school students. Conversely, if sanctions are inappropriate or unfair, they can cause trauma to students. The main conclusions of this study include: limitations in imposing sanctions, reprimands as character education, the balance between reprimands and character education, justice in sanctions, and teacher-student relationships.